2006
DOI: 10.1073/pnas.0601310103
|View full text |Cite
|
Sign up to set email alerts
|

The expression of the clock protein PER2 in the limbic forebrain is modulated by the estrous cycle

Abstract: Daily behavioral and physiological rhythms are linked to circadian oscillations of clock genes in the brain and periphery that are synchronized by the master clock in the suprachiasmatic nucleus. In addition, there are a number of inputs that can influence circadian oscillations in clock gene expression in a tissue-specific manner. Here we identify an influence on the circadian oscillation of the clock protein PER2, endogenous changes in ovarian steroids, within two nuclei of the limbic forebrain: the oval nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
52
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 52 publications
9
52
0
Order By: Relevance
“…The finding of up-regulation of Per1 expression by E 2 may contribute to understand how ER functions to phase shift the circadian rhythms of clock gene expression and to alter the behavior and endocrine rhythms (Morin et al 1977, Thomas & Armstrong 1989, Nakamura et al 2005, Perrin et al 2006. We also find that P 4 efficiently activates the expression of Per1 gene in the uterus, which indicates that P 4 might also have profound effects on circadian clockwork.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The finding of up-regulation of Per1 expression by E 2 may contribute to understand how ER functions to phase shift the circadian rhythms of clock gene expression and to alter the behavior and endocrine rhythms (Morin et al 1977, Thomas & Armstrong 1989, Nakamura et al 2005, Perrin et al 2006. We also find that P 4 efficiently activates the expression of Per1 gene in the uterus, which indicates that P 4 might also have profound effects on circadian clockwork.…”
Section: Discussionmentioning
confidence: 61%
“…It has been demonstrated that estrogen administration alters the circadian rhythms in behavior and endocrine physiology in rodents (Morin et al 1977, Thomas & Armstrong 1989. Recently, it was found that the phase of estrous cycle has a profound effect on the oscillation of PER2 protein within the brain (Perrin et al 2006). It was further reported that chronic treatment with E 2 drastically alters the circadian rhythms of Per1 and Per2 expression in the liver, kidney, and uterus (Nakamura et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Together, these Per2 links the circadian system to ER S Gery et al studies suggest that control of protein turnover is an important feature of circadian regulation. Recent studies in rats showed Per2 is differentially regulated by E2 in specific tissues (Nakamura et al, 2005;Perrin et al, 2006). We found that Per2 mRNA levels were induced by E2 in ERa-positive breast cancer cell lines (Figure 3a), showing that the human Per2 gene is E2-inducible in mammary epithelial cells.…”
mentioning
confidence: 50%
“…Interestingly, Per2 was also suggested to have a role in normal mammary cell differentiation (Metz et al 2006). Studies in rats have shown that estrogen differentially regulates the expression of per1 and per2 in specific brain regions as well as in some peripheral tissues (i.e., liver, kidney, and uterus) (Nakamura et al 2005;Perrin et al 2006). A circadian clock was reported to function in rat ovarian cells, further implicating circadian regulation in local endocrine tissues, as well as its role in the hypothalamopituitary-ovarian axis (Fahrenkrug et al 2006).…”
Section: Hormonesmentioning
confidence: 99%